1994
DOI: 10.1046/j.1471-4159.1994.62031203.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein and Lipid Composition of Radial Component‐Enriched CNS Myelin

Abstract: The radial component is a junctional complex that is believed to stabilize the apposition of myelin membranes in the internode of CNS myelin. Based on our previous finding that the radial component of compact myelin retains its structure in tissue treated with the detergent Triton X‐100, we have attempted to isolate the junctional complex from spinal cord myelin treated with this detergent. Using 0.5% Triton X‐100, our procedures yielded a fraction of isolated myelin that was enriched in well‐preserved radial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The phosphorylated form of MBP is enriched along with cytoskeletal proteins and kinases including MAPK, Fyn, and Lyn within insoluble Triton-X100 membrane domains when extracted from myelin [67,69,70]. These detergent-insoluble membrane domains from myelin also contain the radial component consisting of a series of tight junctions between myelin layers ( [71,72], see also [73]). …”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylated form of MBP is enriched along with cytoskeletal proteins and kinases including MAPK, Fyn, and Lyn within insoluble Triton-X100 membrane domains when extracted from myelin [67,69,70]. These detergent-insoluble membrane domains from myelin also contain the radial component consisting of a series of tight junctions between myelin layers ( [71,72], see also [73]). …”
Section: Discussionmentioning
confidence: 99%
“…Actin and tubulin are present in compact myelin where they may be associated with MBP and the radial component, a series of tight junctions, containing claudin-11 [166], that pass through many layers of myelin [167]. MBP in solution causes polymerization of G-actin into filaments and bundling of the actin filaments [15,17,18,[109][110][111][112] (Fig.…”
Section: Mbp-mediated Interactions With Actin and Tubulin And Effect mentioning
confidence: 99%
“…Detergent extraction of myelin indicates that MBP is located in several different membrane domains or associated with different proteins. Some MBP distributes to two low-density glycosphingolipid/cholesterol-enriched Triton X-100-insoluble fractions, one of which is associated with actin, tubulin, caveolin, and kinases [167,[194][195][196]. Some MBP is also found in the Triton X-100 supernatant associated with MAG, PLP, MAPK, and some phospholipid [197].…”
Section: Mbp-cytoskeleton Interactions In Vivomentioning
confidence: 99%
“…Their expression is enriched during active early myelination in the human and mouse, and in immature OLGs in culture [5][6][7]. These minor MBP isoforms have been observed in the nucleus of primary OLG cultures and OLGs in the mouse brain [25][26][27] and are also enriched in the radial component of compact myelin [28,29]. We have found that full-length 21.5-kDa MBP was still localized primarily to the nucleus despite the presence of the 3′UTR [20][21][22].…”
Section: Introductionmentioning
confidence: 70%